Consecuencias de la noción de existencia. - Láscaris Commeno, Constantino (2009)
With the essay "Consequences of the notion 'existence'", presented in 1976 by the philosopher Constantino Láscaris in the Sixth National Seminar on Demography, the electronic journal "Población y Salud en Mesoamerica" opens the section named Archive with the aim of rescuing for the readers documents, with historical value, on demography and health